Internalization of Islamic Values in Muhammadiyah Elementary Schools - Suyatno Suyatno; Wantini Wantini; Ahmadong Ahmadong; Khamam Khosiin; Abdunrorma Samaalee (Universitas Ahmad Dahlan, 2023)
Muhammadiyah School is one of the largest and oldest private schools that influences the Islamic pattern of Indonesian society. In organizing education, Muhammadiyah uses Islamic core values of progress, namely a Manhaj, in understanding Islamic teachings that are responsive to the progress of the times. This study aims to explore strategies carried out by teachers in internalizing Islamic values in students. The data was collected through semi-structured interviews with 10 teachers in five Muhammadiyah Elementary Schools in Yogyakarta. The data were analyzed using thematic analysis data. The results showed that Islamic values are promoted to be internalized by students through making teachers role models, integrating into school culture, integrating into general subjects, and cooperation between schools and parents. The research findings highlight the importance of involving various components in instilling Islamic values in schools.